Consumer support for a public utilities commission in Hong Kong. (January 2015) - Woo, C.K.; Cheng, Y.S.; Law, A.; Zarnikau, J.; Ho, S.T.; Leung, H.Y.
Abstract: Hong Kong's electricity service is superbly reliable and price-reasonable when compared to those of the major cities in the OECD countries. Based on the rate of return regulation in the U.S., the current scheme of control agreement (SCA) regulating the two local integrated investor-owned utilities (IOUs) will expire in 2018 (or in 2023 after an optional 5-year extension), thus offering an opportune time to consider proposals with long lead time to modify or replace the SCA. The proposals made to date range from modifications of the SCA to electricity market restructure. These proposals, however, overlook two important aspects of regulatory governance: transparency and public involvement. This paper estimates consumer support for the proposal to establish a Hong Kong public utilities commission (HKPUC) to improve the current regulatory process. Based on the responses collected in mid-2014 via a face-to-face survey of 1100 Hong Kong residents, we find that at the 1.5% bill surcharge, about 70% the respondents are estimated to support an HKPUC. Thus, there is sufficient consumer support for a financially viable HKPUC, implying that Hong Kong should consider the possibility of establishing an HKPUC, notwithstanding the substantial challenges to be overcome prior to its implementation. Highlights: Hong Kong's regulatory process lacks transparency and public involvement. A survey data analysis indicates a majority support for a Hong Kong PUC. A Hong Kong PUC can be financially viable without public funding. A Hong Kong PUC proposal deserves further consideration.